Introduction to signal processing, instrumentation, and control an integrative approach - Bentsman, Joseph (Singapore : World Scientific Publishing Co. Pte Ltd., 2016)
"This book stems from a unique and highly effective approach in introducing signal processing, instrumentation, diagnostics, filtering, control, and system integration. It presents the interactive industrial grade software testbed of mold oscillator that captures the mold motion distortion induced by coupling of the electro-hydraulic actuator nonlinearity with the resonance of the mold oscillator beam assembly. The testbed is then employed as a virtual lab to generate input-output data records that permit unraveling and refining complex behavior of the actual production system through merging dynamics, signal processing, instrumentation, and control into a coherent problem-solving package. The material is presented in a visually rich, mathematically and graphically well supported, but not analytically overburdened format. By incorporating software testbed into homework and project assignments, the book fully brings out the excitement of going through the adventure of exploring and solving a mold oscillator distortion problem, while covering the key signal processing, diagnostics, instrumentation, modeling, control, and system integration concepts."--
Mode of access: World Wide Web.
System requirements: Adobe Acrobat Reader.
Title from web page (viewed January 14, 2019).
Includes bibliographical references.
Keywords: Engineering -- Mathematical models; System analysis; Dynamics; Electronic books